Recent advancements in electromagnetic interference shielding of polymer and mxene nanocomposites - Idumah, Christopher Igwe (Polymer-plastics technology and engineering, 2023)
MXene (M-X) and MX@conducting polymeric hybrid nanocomposites inherent conductivity, tunability, flexibility, and miniature thickness present them usable for electromagnetic interference (EMI) shielding applications. The escalating electromagnetic deterioration experienced from electronic gadgets distorts other nearby sensitive electronically affiliated gadgets while adversely affecting human health. Hence, fabrication of M-X@conducting polymeric hybrid nanocomposites especially MX@polyaniline (PAN), MX@polypyrrole (PPy), and M-X@poly (3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT: PSS) nanocomposites for EMI shielding have become very imperative. Therefore, this paper elucidates recently emerging trends in fabrication, characterization, and properties of M-X@CP, as well as non-CP hybrid nanocomposites for EMI shielding applications. Herein, a comparative elucidation of the electrical, magnetic, and other properties of non-CP@M-X and CP@M-X nanocomposites are presented. Additionally, a comparative elucidation of the EMI shielding properties of non-CP@M-X and CP@M-X nanocomposites is additionally elaborated. Furthermore, insight into choice of M-X nanofillers in comparison with carbon nanofillers as well as other nanoparticles for EMI shielding is elucidated.